Estudo da técnica de infusão de resina aplicada à fabricação de compósitos de matriz poliéster reforçados por fibras naturais da Amazônia - RODRIGUES, Jean da Silva (Universidade Federal do Pará, 2017)
In this work were produced unsaturated polyester composites reinforced by fibers of curaua, jute and raffia, arranged in the form of fabric in plan style and aligned fibers. The composites were manufactured by resin infusion process, studying the main parameters that govern the manufacturing method, such as permeability and porosity of the reinforcement and architecture of infusion. Natural fibers were characterized according to their physical, morphological and mechanical properties. The curaua fiber reinforced composites were made using fibers in nature and treated by an alkaline NaOH solution at different concentrations. The composites were characterized in tests of tensile and impact strength, beyond of the determination of their physical properties such as density, porosity and volume fractions of the constituents. The results showed that the composites obtained better performance in tensile and impact were those reinforced with aligned curaua fibers manufactured under vacuum of 101.3 kPa. The evaluation of the cross section of the specimens showed that composites can provide partial saturation of wires or fiber reinforcement due to the vacuum level used mainly in reinforcements in the form of fabric with relatively larger diameter wires. The infusion process proved to be a good method of making composites reinforced with natural fibers, because in addition to being more environmentally friendly because it is a closed mold process, enabled the manufacture of products with high fiber content and good mechanical properties.